Diabetic foot score: a predictive model for leg amputation in patients with diabetic foot disease - Vincent, Agustinus; Soelistijo, Soebagijo Adi; Ardiany, Deasy; Pranoto, Agung; Lusida, Michael Austin Pradipta; Pradhevi, Lukita; Saefudin, Rendra Prasetya (Medical Journal of Indonesia, 2024)
BACKGROUND Patients with diabetes mellitus are at a higher risk for peripheral artery disease (PAD) and diabetic foot disease (DFD), which can ultimately result in leg amputation. This study aimed to develop a novel scoring system to predict the risk of leg amputation using widely available modalities, including demographic characteristics and various laboratory data. METHODS This study was conducted at Dr. Soetomo General Hospital and analyzed risk factors for leg amputation in 99 patients with DFD who underwent leg amputation compared with 80 control patients. This study presented a predictive model for leg amputation in patients with DFD, using odds ratio (OR) analysis and logistic regression approach with confidence intervals (CIs) set at 95%. The data analysis was conducted using SPSS software version 25.0. RESULTS PAD (OR 6.52, 95% CI = 2.19–19.37, p = 0.001), high low-density lipoprotein cholesterol (OR 5.97, 95% CI = 2.31–15.43, p<0.001), type of DFD (OR 4.58, 95% CI = 2.14–9.79, p<0.001), poor glycemic control (OR 4.48, 95% CI = 1.78–11.28, p = 0.001), and neutrophil-to-lymphocyte ratio level (OR 1.04, 95% CI = 1.00–1.07, p = 0.025) were the independent predictors for leg amputation. The predictive model, developed using multivariate analysis with an area under the curve of 89%, optimum threshold of 0.5 (score 6), sensitivity of 84.8%, and specificity of 78.8%, indicating a promising approach for predicting leg amputation outcomes. CONCLUSIONS The newly developed diabetic foot score may assist in making decisions regarding therapeutic options for patients with DFD.